EFFICACY OF INTRALESIONAL BLEOMYCIN INJECTION SCLEROTHERAPY IN MACROCYSTIC LYMPHANGIOMA IN PAEDIATRIC PATIENTS - Hashmi, Shahzada Abdullah Muhammad Khuzaemah Saalim; Hussain, Mukhtar; Ahmad, Shahnab; Gillani, Kashmala (Journal of Ayub Medical College Abbottabad, 2020)
Background This study is aimed to assess the efficacy of intralesional Bleomycin sclerotherapy in macrocystic lymphangioma in children Methods: This prospective observational study included 40 children diagnosed with macrocystic lymphangioma and treated with intralesional injection of Bleomycin from March 2016 to Dec 2018. We excluded all the patients above 12 years of age, lesions with size less than 2 cm, and post-surgical recurrent lesions. The response to the treatment was monitored clinically by assessing length, breadth and area of the lesion and ultrasonographically. Mean follow-up period was 2 years. Study variables were analysed by simple descriptive statistics. Mean and standard deviation were calculated for numerical variables (age). Frequency and percentage were calculated for gender, site, size and type of cystic lymphangioma and total number of treatment sessions. Results: The mean age of patients was 3.51±2.98 years. Out of 40 patients, there were 26 (65%) male and 14 (35%) females with female to male ratio of 1:1.8. The commonest site and type of cystic lymphangioma was neck and macrocystic, i.e., 77.5% and 85% respectively. The pre and post procedure size of lesion was 9.71±3.95cm and 3.11±1.02 cm, respectively. Outcome was excellent in 20% patients, good in 72.5% and poor in 7.5% patients. Conclusions: Intralesional Bleomycin sclerotherapy is effective in the treatment of macrocystic lymphangioma and is found to be harmless as there was no grave complication observed in this study. Keywords: Lymphangioma; Intralesional; Bleomycin